Pengaruh Strategi Pembelajaran Rangkaian Permainan, Indeks Massa Tubuh Terhadap Keterampilan Gerak Dasar Anak Usia Dini - Syahrial Bakhtiar; Khairuddin Khairuddin; Heru Afrian (Jurnal Sporta Saintika, 2019)
This study aims to reveal the effect of learning strategies on conventional and game chains on the ability of students’ object control. It uses quasy experiment design. The population were all kindergarten students in Padang Panjang, amounting to 80 people. The sampling technique is done by purposive random sampling, only students aged 5 to 6 years with a total sample of 80 people. Control object capability data is obtained by giving the TGMD-2 test. Data were analyzed using a two-way variant analysis (ANAVA) technique with a 2x2 factorial design. The results and data analysis show that: 1) There is a difference in the ability of basic movement skills between groups of children who are given a strategy of learning a series of conventional games with a value of Q 3.61>Qtable 2.95). 2) There is a difference in Fundamental Motor Skills between a child with normal BMI and a child with a lean/fat BMI Q count 3.61>Qtable 2.95. 3) There is an interaction between learning strategies with the level of BMI towards the mastery of basic child movement skills which is shown with a value of 0.000<0.05. 4) There is a difference in the ability of basic child movement skills between groups who have a normal BMI given SPRP with conventional learning strategies with the calculation of the value of Q count 7.65>Q table 3.15. 5) There is a difference in the ability of basic movement skills of children between groups of children who have a lean/obese BMI given SPRP with children who are given conventional learning strategies with a Q count value of 4.25>Qtable 3.15.